1994
DOI: 10.1034/j.1600-0501.1994.050101.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the masticatory mucosa on the peri‐implant soft tissue condition

Abstract: The aim of this study was to evaluate the soft tissue conditions at osseo-integrated oral implants in relation to the width of masticatory mucosa. Thirty-nine patients who had received a full-arch fixed bridge reconstruction > or = 10 years ago or a partial reconstruction > or = 5 years ago on a total of 171 implants ad modum Brånemark were included in the study. The examinations involved assessments of plaque, gingivitis, bleeding on probing, probing depth, width of masticatory mucosa and marginal tissue mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
2
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(179 citation statements)
references
References 0 publications
6
163
2
8
Order By: Relevance
“…While Wennström et al (25) have reported that keratinized mucosa does not significantly influence oral hygiene status and soft tissue health, Chung et al (24) have found that the absence of adequate keratinized mucosa in dental implants, especially in posterior implants, was associated with higher plaque accumulation and gingival inflammation but not with increased annual bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…While Wennström et al (25) have reported that keratinized mucosa does not significantly influence oral hygiene status and soft tissue health, Chung et al (24) have found that the absence of adequate keratinized mucosa in dental implants, especially in posterior implants, was associated with higher plaque accumulation and gingival inflammation but not with increased annual bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of keratinized mucosa (KM) surrounding the implant as a barrier against microorganisms and subgingival plaque as a factor for long-term success is discussed [7,8]. KM includes the gingival margin and the mucogingival junction [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto the influence of KM on periimplant health remains to be discussed controversial [8,23,24]. One clinical study investigating implants failed to show the influence of the existence of KM on periimplant soft tissue health [23].…”
Section: Introductionmentioning
confidence: 99%
“…Two millimeters wide band of keratinized tissue has been considered clinically desirable to provide a soft tissue seal around natural teeth [5]. However, controversy still remains over the necessity for a band of keratinized tissue around dental implants [69]. The role of dental plaque in the etiology of peri-implant diseases is well documented in the literature [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some authors have claimed that, with adequate plaque control, peri-implant tissues can be maintained in a healthy state with a minimum amount of keratinized tissue [69]. …”
Section: Introductionmentioning
confidence: 99%